Contemporary Oral Oncology Oral and Maxillofacial Reconstructive Surgery - Kuriakose, Moni Abraham; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This is the third of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume is devoted to the reconstructive surgical techniques used in patients with oral cancer. Following introductory chapters outlining the general principles of reconstructive surgery in the oral cavity and the planning of maxillofacial reconstruction, detailed descriptions of the options and techniques employed in reconstruction of each of the functional subunits are provided. Important technologic advances are also discussed, including image-guided surgery, robotic surgery, and tissue-engineered and prefabricated approaches. Finally, the current status of facial transplantation for maxillofacial reconstruction is reviewed. This volume is intended for both trainees and practicing surgeons.
Overview of Reconstructive Surgery in Oral Cavity Cancer -- Mandibular Reconstruction -- Palato-Maxillary Reconstruction -- Tongue and Floor of mouth Reconstruction -- Cheek Reconstruction -- Lip Reconstruction -- Technologic Advances in Ablative and Reconstructive Surgery -- Prosthetic Reconstruction of the Oro-Facial Region.
Keywords: Dentistry; Medicine; Oncology; Oral surgery; Maxillofacial surgery; Surgical oncology; Medicine & Public Health; Oral and Maxillofacial Surgery; Dentistry; Surgical oncology; Oncology